Vinpocetine is the forthcoming adjuvant agent in the management of COVID-19 - Hayder M Al-kuraishy; Ali I Al-Gareeb; Muyiwa Samuel Fageyinbo; Gaber El-Saber Batiha (Future Science OA)
Vinpocetine (VPN) is an alkaloid derivative of vincamine inhibits phosphodiesterase type 1 that increase cyclic guanosine monophosphate and cyclic adenosine monophosphate. VPN have anti-inflammatory and antioxidant effects with suppression release of pro-inflammatory cytokines. Moreover, VPN mitigates oxidative stress (OS) and inflammatory reactions through inhibition of mitogen-activated protein kinase (MAPK) signaling pathway. Therefore, VPN may decrease hyper-inflammation-induced acute lung injury in COVID-19 through modulation of NF-κB pathway. Taken together, VPN has pulmonary and extra-pulmonary protective effects against COVID-19 through mitigation of OS and hyperinflammation. In conclusion, VPN has noteworthy anti-inflammatory and anti-oxidant effects through inhibition of NF-κB/MAPK signaling pathway so, it may reduce SARS-CoV-2-induced hyper inflammatory and OS.